Factors related to the implementation and scale-up of physical activity interventions in Ireland: a qualitative study with policy makers, funders, researchers and practitioners - Joey Murphy; Fiona Mansergh; Grainne O'Donoghue; Femke van Nassau; Jemima Cooper; Caera Grady; Niamh Murphy; Enrique Garcia Bengoechea; Marie H. Murphy; Benny Cullen; Catherine B. Woods; the I-PARC (BMC, 2023)
Abstract Background Current literature reports a gap between development of effective interventions to promote physical activity and the systematic uptake into real-world settings. Factors relating to implementation and scale-up of physical activity interventions have been examined, however the perspectives of multiple stakeholders from different domains are not well researched. The purpose of this study was to examine the perceived factors related to physical activity intervention implementation and scale-up in different domains from different stakeholders on the island of Ireland. Methods Practitioners, researchers, funders and policy makers in Ireland were invited to take part in a semi-structured interview exploring factors related to the implementation and scale-up of eleven different physical activity interventions. A thematic analysis was conducted to identify factors related to the implementation and scale-up of the included interventions. The data collection and analysis were guided by the Consolidated Framework for Implementation Research. Results Thirty-eight participants took part in the interviews which identified factors related to 1) intervention planning and practical considerations; 2) organisational structures, staffing and resources related to delivery; 3) reflection, evaluation and updating of the intervention; and 4) practical consideration related to scale-up. Furthermore, participants referred to the ongoing commitment, engagement, and support needed throughout the implementation process. Conclusions Future research and practice needs to consider how different factors are experienced at different implementation stages and by the different stakeholder groups involved. The findings highlight multiple inter-related factors that influence the implementation and scale-up of physical activity interventions, but also identifies many strategies that can be utilised to aid future successes.